An analysis of marketing strategies and practices of Aftab Bahumukhi Farm Limited - Moinuddin, Md. Khawza (BRAC University, 2012)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.